Anúncios em outdoors da década de 60 versus anúncios em outdoors contemporâneos: uma análise comparativa dos aspectos semióticos visuais. - Pontes, Andresa Maria de Lima (2020)
This dissertation proposes to analyze comparatively the semiotic visual aspects of the announcements of vehicles in billboards of the decade with announcements in contemporary billboards and its relation with the verbal text. In order to do so, the specific objectives are: to identify the visual semiotic features of advertisements in the 1960 and in contemporary ads from the Visual Design Grammar (GDV), to verify the status relationship between verbal / written text and imagery of 60's billboard ads and contemporary billboard ads and reflect on the role of the image in the 1960s ads and contemporary ads. Thus, a theoretical study situated in the field of the foundations of the genre and centered in the dialogical perspective of Bakhtin (2002) was constructed. A reflection on the characteristics, the compositional organization and historical evolution of the ad genre was carried out. Subsequently, an investigation was made into the history of the billboard. For the brief study on the Outdoor as support for multimodal genres, we tried to reflect on the support in the textual perspectives, by Marcuschi (2003); Discourse Analysis, by Maingueneau (2012) and Sociorhetoric, by Bonini (2003). Then, to reach the research objective, reflections on the status of the image-text relationship system, by Martinec and Salway (2005), reflections on the text-image relationship from Santaella (2012) were made and a a study of multimodality that is situated in the field of the foundations of social semiotics from the works of Kress and Van Leeuwen (2006) and Van Leeuwen (2005). The methodology adopted was based on a descriptive and qualitative study. To do so, 20 ads were selected on 60's billboards and 20 ads on contemporary billboards. Of these 20 ads, a qualitative cut was made of 7 ads in billboards in the 60s and 7 ads in contemporary billboards. During the analysis, in addition to significant interactions with the observer, multimodal advances in contemporary advertisements were perceived. Significant changes in the status relationship were still noted, since contemporary ads showed a preference for dominance of the image over the verbal text. As for the roles between verbal / written and imaginary text on billboards of the 60s and on contemporary billboards, the images of contemporary advertisements had expressive unequal image-text relations, since the image presented superior status, that is, the image was more informative in relation to the verbal text. Thus, the ads had a significant preference for dominance of the image in relation to the verbal text.